Estudo sintático-semântico das posições de adjetivos no português e mandarim - Lang, Si (2014)
The aim of this paper is to research the position of adjectives in both Mandarin and Brazilian Portuguese, with respect to syntax and semantics. When compared to Mandarin which has a more rigid order, Brazilian Portuguese has the greater flexibility in the word order of the noun phrase, especially, the adjective position. Firstly, the relevant studies concern about adjectives of the two languages are taken up, with the objective of showing what they form a class of words with a peculiar syntactic-semantic behavior. Secondly, this paper also presents the syntactic approaches that explain the flexibility of the position of adjectives in Brazilian Portuguese in an interface with semantics. Meanwhile, proposals are illustrated, in which describe syntactic and semantic properties with regard to the adjective positioning in Mandarin. Lastly, this work discusses the limitations and reflections of the adopted theories. In addition, the analysis of adjectives within a noun phrase of Brazilian Portuguese and Mandarin, leads proposing a syntactic-semantic proximity between the two both languages in some extent